Marine Conservation in the East Sea: Legal, Political, and Economic Constraints on Vietnam’s Environmental Governance - Hung Chu Manh; Hoang Do Qui; Tuan Vu Van (Faculty of Law, Sriwijaya University, Indonesia, 2026)
The study investigated the challenges and prospects of marine resource management in regions with overlapping maritime claims. It particularly focused on Vietnam’s efforts to conserve Vietnam’s East Sea. Geopolitical constraints, legal uncertainties, and economic mechanisms are the main factors that impede the effective management of maritime resources in disputed areas, as seen in the 1982 UNCLOS and regional legal regimes. This qualitative study employed a structural, analytical approach to exploit secondary resources, using case studies and literature analysis to evaluate the effectiveness of Vietnam’s policies in sustainable fisheries management, marine protected areas, and international collaborations with neighbouring countries. The results reveal that Vietnam has made progress in adopting preventive measures pursuant to the 1982 UNCLOS; however, it also faces serious challenges in implementing them, including insufficient regional cooperation, territorial disputes, and scientific uncertainties. The study underscores the urgent need for a robust legal and institutional framework to facilitate sustainable resource management across overlapping maritime claims. Therefore, the findings highlight the necessity of enhanced cooperation, stronger enforcement of legal frameworks, and greater scientific collaboration to address the conservation challenges of Vietnam’s East Sea.